Effects of hyperlipidaemia on glucocorticoid metabolism: results of a randomized controlled trial in healthy young women - Mai, Knut; Reinecke, F.; Andres, J.; Bobbert, T.; Kraatz, J.; Wudy, S. A.; Hartmann, M.f.; Maser-Gluth, Christiane; Pfeiffer, A.f.h.; Spranger, J. (Clinical endocrinology, 2011)
Objective: It is well established that the hypothalamic-pituitary-adrenal (HPA) axis is altered in obese individuals. Hyperlipidaemia with elevated levels of free fatty acids (FFAs) is also frequently seen in obesity and in the metabolic syndrome. We hypothesized, therefore, that hyperlipidaemia may alter the activity of the HPA axis. Patients and methods: The effects of hyperlipidaemia, including increased circulating FFAs, on ACTH secretion and cortisol metabolism were analysed in 13 healthy young women during the early follicular phase of two subsequent cycles. We administered a 20% lipid/heparin (LHI) or a saline/heparin infusion (SHI) using a crossover design in random order for 330 min. A detailed characterization of glucocorticoid metabolism was performed by measurement of plasma ACTH, cortisol and urinary excretion rates of adrenal glucocorticoids and the glucocorticoid metabolites. Results: We observed that LHI-induced hyperlipidaemia elevated serum cortisol levels compared to SHI. No changes in plasma ACTH levels, daily urinary excretion rates of adrenal glucocorticoids, glucocorticoid precursors/metabolites and the calculated activities of the 5α-reductase, 3β-hydroxysteroid dehydrogenase (HSD), 11-, 17-, 21-hydroxylase and 11β-HSD 1 or 2 were found. Conclusion: Our randomized controlled trial suggests that the adrenal sensitivity to ACTH may be enhanced by LHI-induced hyperlipidaemia in normal-weight healthy young women. This effect might contribute to the disturbances of the HPA axis described in women with abdominal obesity and impaired lipid metabolism.
Gesehen am 09.08.2022